Understanding patterns of receipt and consumption of IFA supplements during pregnancy: Empirical considerations for measuring coverage - Nguyen, Phuong Hong; Manohar, Swetha; Kim, Sunny S.; Pandya, Niharika; Kapoor, Rati; Munos, Melinda (Elsevier, 2024)
Objectives: Daily iron-folic acid (IFA) supplementation during pregnancy is a core intervention in low- and middle-income countries. Yet, there is a concern of poor validity and biased population coverage estimates using maternal reports of total number of IFA supplements. This study examined patterns of IFA receipt and consumption among pregnant women in India and identified considerations for measuring coverage of IFA supplementation.